Analisis Sistem Pengawasan MUI Terhadap Hotel Syariah Di Kota Medan - Riyan Pradesyah; AL Bara (AGHNIYA : Jurnal Ekonomi Islam, 2020)
The purpose of this study, to find out how the supervision system carried out by the Indonesian Ulema Council (MUI) against Sharia Hotels in the city of Medan. The development of sharia hotels in Indonesia continues to experience a significant increase, this can be seen from the many sharia hotel deals that occur to the public, and also the large number of sharia hotels that stand in the midst of the community. This development is certainly a matter of pride for Muslims, where Islamic principles can again be accepted by the wider community. The development of sharia hotels is a real form, that sharia principles can not only be used by Muslim communities, but also can be used by the wider community. So now sharia hotels can continue to show their existence in the community. So when this happens, there must be a clear system of supervision, which must be carried out by the MUI, with the aim of maintaining the purity of sharia that is applied to sharia hotels in the city of Medan. When viewed from the development of sharia principles applied in financial institutions, it can be seen a strict system of supervision from the MUI, in order to continue to apply sharia principles purely. Supervision carried out by the MUI, placed the Sharia Supervisory Board (DPS) in each of the Islamic financial institutions. The research conducted is qualitative research with a descriptive approach. Where the method used to obtain maximum results, must use in-depth interviews (depth interviews) to the Indonesian Ulema Council (MUI) in the city of Medan, and make observations and documentation. The data analysis technique used in this study was interview.Keywords: Sharia Hotels, Supervision